2021
DOI: 10.2991/assehr.k.210305.052
|View full text |Cite
|
Sign up to set email alerts
|

Examining Middle School Student’s Lower Order Thinking Skill

Abstract: Focusing in Higher Order Thinking Skill (HOTS) has been main goal in many education curriculums around the world including in Indonesia. Even though the ultimate goal is usually for students to achieve HOTS, it is also important to make sure student already mastered Lower Thinking Skill (LOTS) since it is a prerequisite in the process of using higher-order thinking. Therefore, the goal of the study is to examine student's achievement on LOTS. The paper pencil test with multiple choice format was developed and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 9 publications
(10 reference statements)
0
4
0
Order By: Relevance
“…The development of these cognitive categories is contextdependent and closely related to the expertise and training of those who use them in specific settings, leading to the need for strong targeting if we want to obtain the most accurate results that can be replicated in similar contexts. Therefore, further research is needed on the practical delivery of cognitively challenging tasks aimed at optimising CLIL learners' thinking skills (Barut and Wijaya, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The development of these cognitive categories is contextdependent and closely related to the expertise and training of those who use them in specific settings, leading to the need for strong targeting if we want to obtain the most accurate results that can be replicated in similar contexts. Therefore, further research is needed on the practical delivery of cognitively challenging tasks aimed at optimising CLIL learners' thinking skills (Barut and Wijaya, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Alcaraz-Mármol (2018) indicated that controlled activities associated with LOTS were implemented more frequently than other more complex activities in bilingual teaching in Spain. Similarly, Barut and Wijaya (2021) concluded that most CLIL practice in Manggarai Timur Regency was aimed at recall and comprehension rather than the development of more complex cognitive categories. Based on the knowledge and information derived from the literature, one can conclude the relevance of exploring how LOTS has been incorporated into CLIL teaching practice in order to foster students' dual-focus learning.…”
Section: Introductionmentioning
confidence: 99%
“…The organization for Economic Co-operation and Development (OECD) highlighted one of the elements behind Indonesia's lagging as a focus on Lower Order Thinking Skills (LOTS) in the learning process. With this style of teaching and learning, there is no systematic strategy for strengthening minds in the 21st century (Barut & Wijaya, 2021;Qasrawi & Beniabdelrahman, 2020;Tsaparlis, 2020). Teaching and learning activities which are increasingly dominated by explanations from teachers make learning boring, one-way, and less able to create ways that educate and empower students' learning abilities to discuss, conduct case surgery, solve the problem, experiment, observe, etc.…”
Section: Introductionmentioning
confidence: 99%
“…The organization for Economic Co-operation and Development (OECD) highlighted one of the elements behind Indonesia's lagging as a focus on Lower Order Thinking Skills (LOTS) in the learning process. With this style of teaching and learning, there is no systematic strategy for strengthening minds in the 21st century (Barut & Wijaya, 2021;Qasrawi & Beniabdelrahman, 2020;Tsaparlis, 2020). Teaching and learning activities which are increasingly dominated by explanations from teachers make learning boring, one-way, and less able to create ways that educate and empower students' learning abilities to discuss, conduct case surgery, solve the problem, experiment, observe, etc.…”
Section: Introductionmentioning
confidence: 99%